The Eucharist in modern philosophy - Tilliette, Xavier (The Catholic University of America Press, 2023)
"This volume looks at how various ,modern philosophers, such as Descartes, Leibniz, Hegel, Blondel, and Marion, as well as poets and mystics, such as de Chardin, Simone Weil, and Paul Claudel, thought extensively about the question of the Eucharist. The book demonstrates that the Eucharist has been, and will likely continue to be, a major impetus for philosophical reflection"--